The effect of equalization of public health services on the health China's migrant population: Evidence from 2018 China Migrants Dynamic Survey - Su, BinBin; Wu, Yu; Yihao, Zhao; Chen, Chen; Panliang, Zhong; Zheng, Xiaoying (Frontiers in Public Health, 2023)
Objectives China has implemented an equalization of public health Services policy for migrants in 40 pilot cities since 2013. The main objective of this study is to explore the effect of this migrant-based reform policy on the health status of the migrant population in China. Methods Using the China Migrants Dynamic Survey (CMDS), we included 152,000 migrants aged 15 years or over in 2018. Standardized questionnaires were used to collect socio-economic information and self-reported health status. The Associations between the equalization of public health services and health status were estimated using Multiple regression estimation models and Propensity Score Matching (PSM) methods. Results Public health equalization reform in China has a significant and positive effect on the health status of the migrant population (β = 0.033, p < 0.001). Compared to males, higher income, under 60 years of age, inter-provincial mobility, and migrants those already living in urban areas, the equalization of public health Services had shown more significant positive effects on the groups who were inter-provincial migration (β = 0.055, p < 0.001), females (β = 0.055, p < 0.001), having low-income (β = 0.077, p < 0.001), aged over 60 years old (β = 0.191, p < 0.001), and living in rural areas (β = 0.038, p < 0.001). And multiple robustness tests prove that the above results are reliable. Conclusions and implications Our findings confirmed the positive health effect of the equalization of public health services reform on china's migrant population, especially among vulnerable groups such as those in low income groups, in rural areas and females. And we recommend that it is necessary to further promote the practices and experiences of the pilot cities. First, strengthen health education for the mobile population and improve their health literacy. Second, further increase the financial investment to improve the coverage of public health services and the equity in resource allocation among regions. Last, strengthen the information-based management of the migrant population and prevent and control infectious diseases.